Variations in genome-wide gene expression in identical twins – a study of primary osteoblast-like culture from female twins discordant for osteoporosis - Beresford Jon N; Hampson Geeta; Mak Ying T; Spector Tim D (BMC Genetics, 2004)
Abstract Background Monozygotic twin pairs who are genetically identical would be potentially useful in gene expression study for specific traits as cases and controls, because there would be much less gene expression variation within pairs compared to two unrelated individuals. However the twin pair has to be discordant for the particular trait or phenotype excluding those resulting from known confounders. Such discordant monozygotic twin pairs are rare and very few studies have explored the potential usefulness of this approach. Results We studied genome-wide gene expression in primary osteoblast-like culture from marrow aspirates obtained from three pairs of monozygotic twins. We used the latest Affymetrix microchip contains probe sets for more than 20,000 genes. Two pairs were discordant for bone mineral density at the hip by more than one standard deviation, and the third pair was unrelated concordant and used as control. Only 1.5% on average of genes showed variation in expression within pairs as compared to 5% between pairs or over 15% from the literature. Importantly we identified several groups of genes showing variations within the discordant pairs and not within the concordant pair such as chondroitin beta 1,4 N-acetylgalactosaminyltransferase, inhibin beta A, interleukin 1 beta and colony stimulating factor 1 macrophage. These genes are known to have potential roles in bone physiology relating to bone density, osteoporosis and osteoarthritis. Conclusion Using the example of osteoblast-like cells in our monozygotic discordant twins for osteoporosis, we identified genes showing differential expression. Although without further experiment, we cannot confirm or conclude these are genes definitely related to bone physiology, we believe we have shown the potential and cost-effectiveness of further gene expression studies in discordant monozygotic twin pairs. A replication study for confirmation is essential.